A = cos ( 2 0 1 3 π ) + cos ( 2 0 2 1 π ) + cos ( 2 0 2 9 π ) + cos ( 2 0 3 7 π )
Find the value of ⌊ 1 0 0 0 A ⌋ .
Notation:
⌊
⋅
⌋
denotes the
floor function
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you directly showed that cos(2pi/5)+cos(4pi/5)=-1/2 ?
Log in to reply
See Proof for k = 0 ∑ n − 1 cos ( 2 n + 1 2 k + 1 ) = 2 1 .
Note that the 5 roots of z 5 = 2 1 + i are e i 2 0 ( 8 k + 5 ) π where k = 0 , 1 , 2 , 3 , 4 .
The sum of roots is 0, by Vieta formula, which implies that the real part of the sum is also 0. Hence k = 0 ∑ 4 Re ( e i 2 0 ( 8 k + 5 ) π ) = 0 . Now
cos ( 2 0 5 π ) + cos ( 2 0 1 3 π ) + cos ( 2 0 2 1 π ) + cos ( 2 0 2 9 π ) + cos ( 2 0 3 7 π ) = 0
So, A = cos ( 2 0 1 3 π ) + cos ( 2 0 2 1 π ) + cos ( 2 0 2 9 π ) + cos ( 2 0 3 7 π ) = − cos ( 2 0 5 π ) = − 2 1 ≈ − 0 . 7 0 7 1
Finally, ⌊ 1 0 0 0 A ⌋ = ⌊ − 7 0 7 . 1 ⌋ = − 7 0 8 .
A = cos ( 2 0 1 3 π ) + cos ( 2 0 2 1 π ) + cos ( 2 0 2 9 π ) + cos ( 2 0 3 7 π ) = 2 cos ( 4 0 5 0 π ) ⋅ cos ( 4 0 2 4 π ) + 2 cos ( 4 0 5 0 π ) ⋅ cos ( 4 0 8 π ) = 2 cos 4 5 π { cos ( 5 3 π ) + cos ( 5 π ) } = 2 2 cos ( 4 5 π ) = cos ( π + 4 π ) = − 2 1 = − 0 . 7 0 7 1 0 6 7 8 1 2 Therefore, ⌊ 1 0 0 0 A ⌋ = ⌊ − 7 0 7 . 1 0 6 7 8 1 2 ⌋ = − 7 0 8
Note cos ( 5 π ) = 1 − 2 sin 2 ( 1 0 π ) = 1 − 2 ( 4 5 − 1 ) 2 = 4 5 + 1 = 2 ϕ cos ( 5 3 π ) = − sin ( 2 π + 1 0 π ) = − sin ( 1 0 π ) = − ( 4 5 − 1 ) = 4 1 − 5 = − 2 ϕ − 1 cos ( 5 π ) + cos ( 5 3 π ) = 4 5 + 1 + 4 1 − 5 = 2 1
Problem Loading...
Note Loading...
Set Loading...
A = cos ( 2 0 1 3 π ) + cos ( 2 0 2 1 π ) + cos ( 2 0 2 9 π ) + cos ( 2 0 3 7 π ) = cos ( 5 2 π + 4 π ) + cos ( 5 4 π + 4 π ) + cos ( 5 6 π + 4 π ) + cos ( 5 8 π + 4 π ) = 2 1 ( cos ( 5 2 π ) − sin ( 5 2 π ) + cos ( 5 4 π ) − sin ( 5 4 π ) + cos ( 5 6 π ) − sin ( 5 6 π ) + cos ( 5 8 π ) − sin ( 5 8 π ) ) = 2 1 ( cos ( 5 2 π ) + cos ( 5 4 π ) + cos ( 5 6 π ) + cos ( 5 8 π ) − sin ( 5 2 π ) − sin ( 5 4 π ) − sin ( 5 6 π ) − sin ( 5 8 π ) ) = 2 1 ( cos ( 5 2 π ) + cos ( 5 4 π ) − cos ( 5 π ) − cos ( 5 3 π ) − sin ( 5 3 π ) − sin ( 5 π ) + sin ( 5 π ) + sin ( 5 3 π ) ) = 2 1 ( − 2 1 − 2 1 ) = − 2 1 ≈ − 0 . 7 0 7 1 See proof below.
Therefore, ⌊ 1 0 0 0 A ⌋ = − 7 0 8 .
Reference: Proof for k = 0 ∑ n − 1 cos ( 2 n + 1 2 k + 1 ) = 2 1